Potensi Habbatussauda ( Nigella Sativa ) Terhadap Pencegahan Demensia Alzheimer - Arifin, Hasanul (Buletin Farmatera, 2024)
Abstract: Dementia is a progressive and degenerative clinical syndrome, that affects memory, thinking ability, behaviour, emotions and personality that interfere with daily life activities. The aetiology of dementia is linked to the involvement of vascular, inflammatory, oxidative stress and neurotoxicity that causes neurodegenerative brain pathologies that can contribute to cognitive impairment and dementia. Multidomain interventions targeting multiple risk factors for effective prevention including dietary supplements from traditional plants. Nigella sativa (NS) is a traditional plant native to the Mediterranean Area and Southwest Asia that has long been used to maintain human health. Nigella Sativa has a significant content of thymoquinone (TQ) as a bioactive element of 30-48% of the total NS compounds. Several in vitro and in vivo preclinical studies and clinical trials that are still limited to non-dementia humans show that TQ has a positive effect on cognitive impairment through oxidative stress control mechanisms, vascular health, anti-inflammatory, maintenance of nerve cell integrity and improvement of neurotrophic regulatory factors which are promising in preventing cognitive decline. Nigella sativa serves as a potential dietary supplement to prevent the progression of Alzheimer's disease but requires long-term investigation and follow-up research to test safety and toxicity and compare its effectiveness at different stages of dementia such as Alzheimer's disease.